2017
DOI: 10.1021/acs.energyfuels.7b01067
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Mechanisms Governing Wettability Alteration by Chemically Tuned Waterflooding: A Review

Abstract: Enhanced oil recovery (EOR) techniques are aimed at improving the recovery efficiency of mature oil fields in secondary and tertiary recovery modes. In particular, chemically tuned waterflooding (CTWF) has been a rising EOR technique toward improving oil recovery from rocks that are difficult to produce due to their initial wetting state, e.g., oil-wet and intermediate-wet. With an increasing oil-wetting affinity of a reservoir rock, extraction of oil becomes more challenging. As such, wettability alteration h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 79 publications
1
36
0
Order By: Relevance
“…Different physicochemical mechanisms have been proposed to validate wettability alteration as one of the primary causes of oil recovery enhancement by LSW flooding in sandstone and carbonate rocks. These mechanisms are classified as salting-in, multiple ion exchange (MIE), fines migration, EDL expansion, mineral dissolution, and pH modification (Purswani et al 2017).…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different physicochemical mechanisms have been proposed to validate wettability alteration as one of the primary causes of oil recovery enhancement by LSW flooding in sandstone and carbonate rocks. These mechanisms are classified as salting-in, multiple ion exchange (MIE), fines migration, EDL expansion, mineral dissolution, and pH modification (Purswani et al 2017).…”
Section: Mechanismsmentioning
confidence: 99%
“…To illustrate the phenomenon of rock dissolution in carbonate reservoirs, zeta potential measurements were performed by Yousef et al (2011), as it has been widely applied for determining the surface charge of a rock in a particular brine environment (Esmaeili et al 2016;Rahbar et al 2017;Vinogradov et al 2010). Their results revealed a reduction of the carbonate surface zeta potential with a decrease in brine salinity, which suggested that Ca 2+ ions migrated from the rock surface toward the low-salinity brine to re-establish chemical equilibrium between the bine and rock (Purswani et al 2017). Moreover, the decrease in the positive charge on the carbonate surface in presence of low-salinity water led to the expansion of the electric double layer (EDL) and resulted in a thicker, more stable water film.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of different proposed mechanisms conducted by Sohal et al (2016) and Afekare and Radonjic (2017) also suggested favorable wettability alteration as the main underlying factor associated with LSWF/MWF successes. It is worth mentioning here that whereas wettability alteration is just the consequence of oil recovery process, the real mechanism could be a combination of different underlying processes whose net outcome is the visible change in wettability (Purswani et al 2017). Lashkarbolooki et al (2016) and Myint and Firoozabadi (2015) conducted extensive reviews of the probable mechanisms of action regarding to the wettability alteration and came to the conclusion that expansion of electric double layer, multicomponent ionic exchange, salt-in effect and dissolution of calcite minerals are possible mechanisms responsible for the wettability alteration of oil-wet carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…This review addresses the subjects of current interests about gathering information on past and recent developments, and challenges of brine-dependent recovery processes in sandstone and carbonate rocks. There have been several recent summaries that discussed different aspects of this subject [75][76][77][78][79][80][81][82][83]; hence, this review builds upon these summaries to further explore the published data to build theoretical understanding and identify potential opportunities for further investigation. Overall, the outcome of this review will potentially be of immense benefit to the oil industry.…”
Section: Introductionmentioning
confidence: 99%